Professional identity crisis : balancing the internal and external perception of professional image - Tomo, Andrea (Emerald points., 2019)
The book deals with an increasingly crucial but under-researched topic, that is the crisis of theprofessional identity. It will be both theoretically driven and empirically focused, also attempting toprovide useful practical recommendations.